Mengapa Negosiasi Internasional Gagal? Menjelaskan Kegagalan Perundingan Denuklirisasi Amerika Serikat- Korea Utara 2019 - Mohamad Rosyidin; Ayu Sabrina; Annisa Antania Hanjani; Indra Kusumawardhana (Department of International Relations, Universitas Andalas, 2021)
This article aims to explain the failure of US-North Korea’s denuclearization negotiation in 2019. There has not been research on this topic. In general, existing literature proposes four factors that explain the failure of international negotiation, namely, actor, structure, strategy, and process. This article contributes to existing literature by adding another variable in explaining diplomatic failure. Using Charles Kupchan’s concept of unilateral accommodation, this article argues that the failure of US-North Korea’s denuclearization negotiation in 2019 is caused by the failure at the unilateral accommodation stage due to US distrust over North Korean’s commitment in dismantling its nuclear program. Despite the fact that North Korea has sent a positive signal to the US – for example by destroying its nuclear facilities and returning US prisoners of war and soldiers’ body – the US remains unfazed. This article demonstrates that the negotiation process is largely determined by the first stage in which each party gives concessions in order to create mutual trust.